Chemical Composition and Porosity Characteristics of Various Calcium Silicate-Based Endodontic Cements. (1st February 2018) - Chang, Seok Woo
Abstract : Chemical composition and porosity characteristics of calcium silicate-based endodontic cements are important determinants of their clinical performance. Therefore, the aim of this study was to investigate the chemical composition and porosity characteristics of various calcium silicate-based endodontic cements: MTA-angelus, Bioaggregate, Biodentine, Micromega MTA, Ortho MTA, and ProRoot MTA. The specific surface area, pore volume, and pore diameter were measured by the porosimetry analysis of N2 adsorption/desorption isotherms. Chemical composition and powder analysis by scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) were also carried out on these endodontic cements. Biodentine and MTA-angelus showed the smallest pore volume and pore diameter, respectively. Specific surface area was the largest in MTA-angelus. SEM and EDS analysis showed that Bioaggregate and Biodentine contained homogenous, round and small particles, which did not contain bismuth oxide.